2007
DOI: 10.1016/j.enggeo.2007.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Advanced DInSAR analysis on mining areas: La Union case study (Murcia, SE Spain)

Abstract: The town of La Union (SE, Spain) is located within a metal mining area that has been exploited since the Roman period. This historic exploitation has left behind a high concentration of abandoned underground mining galleries. Currently, an industrial area is subsiding due to the collapse of one of these galleries in May 1998. In this paper, an advanced Differential Interferometry SAR (DInSAR) method called the Coherent Pixels Technique (CPT) has been used to study the subsidence phenomena for two time interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
56
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(60 citation statements)
references
References 18 publications
0
56
0
4
Order By: Relevance
“…Many authors have reported that the DInSAR results have shown good agreement when compared with groundbased measurements 4,13,14,16,34,35,37,42,45,58,59,61,66,67 and provide reliable estimates of subsidence, particularly in an urban environment. A comparison of precise levelling and persistent scatterer SAR interferometry has been done 58,59 and PSI results show good agreement with the levelling data.…”
Section: Assessment Of Sar Interferometric Measurementsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many authors have reported that the DInSAR results have shown good agreement when compared with groundbased measurements 4,13,14,16,34,35,37,42,45,58,59,61,66,67 and provide reliable estimates of subsidence, particularly in an urban environment. A comparison of precise levelling and persistent scatterer SAR interferometry has been done 58,59 and PSI results show good agreement with the levelling data.…”
Section: Assessment Of Sar Interferometric Measurementsmentioning
confidence: 99%
“…Herrera et al 44 using CPT and TerraSAR-X data while monitoring an urban subsidence in Murcia, Spain, have reported an average rate of subsidence from -5 mm/yr to -35 mm/yr. In another study using CPT, Herrera et al 37 while monitoring metal mining area in Murcia, have demonstrated that deformation values with DInSAR (using ERS 1/2 and Envisat images) on comparison with the topographical levelling network measurements of the same period gave an absolute average difference of 0.7 cm with a standard deviation of 0.5 cm.…”
Section: Assessment Of Sar Interferometric Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…54 Most of the geodetic techniques, including GPS, allow measuring recent short- The technique was first applied to single deformation events such as ground 64 motion in agricultural fields related to changes in the soil moisture caused by irrigation 65 (Gabriel et al, 1989) or ground displacement associated with the 1992 Landers, 66 California earthquake (Massonet et al, 1993). Subsequently, differential SAR 67 interferometry has been used to study different types of surface deformation, including 68 active faulting and preseismic, coseismic and postseismic displacements (Massonnet et Herrera et al, 2007), multiyear and seasonal uplift and subsidence controlled by 75 groundwater withdrawal and recharge (Amelung et al, 1999;Galloway et al, 1998;76 Hoffman et al, 2001), shrink-swell cycles in soils related to rainfall (Massonnet and 77 Feigl, 1998), the identification and anticipation of sinkholes in karst areas (Baer et River valley (Quirantes, 1978). Figure 5) and with the maximum number of significant rainfall events (>20 mm) over 481 the periods studied.…”
mentioning
confidence: 99%